Incidence and reasons for biologic and targeted synthetic DMARD switching in juvenile idiopathic arthritis: a real- life stratified analysis - Daniel Clemente; Leticia Leon; Juan Carlos Nieto-Gonzalez; Alina Lucica Boteanu; Laura Trives Folguera; Antía Asunción García-Fernández; Helena Amar Muñoz; Aliuska Palomeque; Juan Carlos López Robledillo; Lydia Abasolo (Pediatric Rheumatology Online Journal)
Abstract Background Switching biologic and targeted synthetic DMARDs (b/tsDMARD) is common in juvenile idiopathic arthritis (JIA) patients, though information about how this switching is done is scarce. This study aimed to determine the incidence rate, reasons for switching, and risk factors associated with switching due to inefficacy across different JIA subtypes. Methods A multi-hospital electronic health record (EHR) registry was used to identify JIA patients prescribed ≥ 1 b/tsDMARD between 2000 and 2024. Patients were categorized into four JIA subgroups: oligoarticular, polyarticular, juvenile spondyloarthritis (JSpA), and systemic JIA. The primary outcomes were switching rates and switching due to inefficacy. Incidence rates (IR) were calculated per 100 patients-year. Cox multivariate regression analyses were run to assess the risk of b/tsDMARDs switching due to inefficacy, expressed as hazard ratio (HR) and 95% CI. Results In our JIA registry, a total of 213 patients received a b/tsDMARD, with a total of 321 courses. The mean age at onset was 6.03 ± 4.44 years and 66.20% were females. The oligoarticular course group included 69 patients (32.39%), the polyarticular group 76 patients (35.68%), the JSpA group 43 patients (20.19%), and the systemic group 25 patients (11.74%). We found a total of 100 b/tsDMARD switches, with 32.05% of patients switched at least once. The systemic JIA group was more likely to swapping (p ≤ 0.001). Through the study period, the overall switching incidence rate was 7.32 [6.01–8.90] per 100 patients-year. In the stratified analysis across JIA groups, the systemic JIA group exhibited the highest incidence (IR:17.01 [11.20-25.84]). Regarding switching due to inefficacy, global incidence was 4.53 [3.53–5.82] and again systemic JIA was the group with the highest incidence (IR: 9.28 [5.27–16.34]). Still, the adjusted multivariate final model confirms that systemic JIA needed more switching due to inefficacy (2.43 [1.01–5.89], p = 0.04). Conclusion This real-life study provides data on different switch patterns in various subtypes of JIA, confirming that patients with systemic JIA needed more switching, did more swapping strategies, and had more risk for switching due to inefficacy.